National Renaissance and the Development of Porcelain Art in Sweden: 1850–1910s - Yarmosh, Anastasiia S. (Actual Problems of Theory and History of Art, 2016)
Special features in cultural development and artistic environment of the second half of the 19th century in Sweden stemmed from historical processes and events connected with the rise of the national movement. Announced in 1811, during the session of the Swedish Association in Stockholm, the idea of the cultural alliance of Nordic countries and the one of the turning back to ancient art, to the origins, found their expression in various forms of art in Sweden. The birth of the “Northern Movement”, which followed it, revived the interest in the authentic old periods of Scandinavian history. To a large extent, it determined the nature of artistic imagery in visual, monumental, and applied arts of the “Nordic French”. In Swedish porcelain production, these trends can be traced in several stages: from the historicism, with its emphasis on perception and new reading of the literary and material monuments of the Viking Age, to a completely new imagery, subjects, and forms of Swedish Art Nouveau.
Keywords: Sweden; national art; historicism; porcelain; Rörstrand; Gustavsberg; Alf Vallander